2023
DOI: 10.1111/his.14907
|View full text |Cite
|
Sign up to set email alerts
|

Bronchiolar adenoma with squamous metaplasia: a distinct phenotype

Abstract: Aims: Pulmonary bronchiolar adenoma is a benign lung tumour characterised by nodular proliferation of bilayered bronchiolar-type epithelium with a continuous layer of basal cells. The aim of this study was to describe a distinct and rare histological type of pulmonary bronchiolar adenoma: bronchiolar adenoma with squamous metaplasia. Methods and results: We examined the clinicopathological, immunohistochemical, and molecular characteristics of five cases (two cases from the same patient). The samples were hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In addition, mixed squamous cell and glandular papilloma is a rare benign tumor with similar morphology and cell composition to BA/CMPT, which can be distinguished by the anatomical site of the lesion ( 42 ), or the presence or absence of AKT1 mutations ( 45 ). Recently, Teng et al ( 46 ) reported 5 cases of BA with squamous metaplasia. Interestingly, none of the cases had mucinous cells, and sheet-like spindle-oval cells with squamous metaplasia was more easily misdiagnosed as pulmonary sclerosing pulmonary (PSP), the expression level of TTF-1 is the key to distinguish between them.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mixed squamous cell and glandular papilloma is a rare benign tumor with similar morphology and cell composition to BA/CMPT, which can be distinguished by the anatomical site of the lesion ( 42 ), or the presence or absence of AKT1 mutations ( 45 ). Recently, Teng et al ( 46 ) reported 5 cases of BA with squamous metaplasia. Interestingly, none of the cases had mucinous cells, and sheet-like spindle-oval cells with squamous metaplasia was more easily misdiagnosed as pulmonary sclerosing pulmonary (PSP), the expression level of TTF-1 is the key to distinguish between them.…”
Section: Discussionmentioning
confidence: 99%
“…Teng et al 9 examines five cases of proximal type BA showing 'stromal' expansion characterised by extensive squamous metaplasia. In all five samples, BRAF V600E mutations were detected in both the basal cells and metaplastic squamous cells, indicating that the squamous metaplasia is a component of the BA.…”
mentioning
confidence: 99%